Magnetic resonance linear accelerator technology and adaptive radiation therapy: An overview for clinicians. (18th November 2021) - Hall, William A.; Paulson, Eric; Li, X. Allen; Erickson, Beth; Schultz, Christopher; Tree, Alison; Awan, Musaddiq; Low, Daniel A.; McDonald, Brigid A.; Salzillo, Travis; Glide‐Hurst, Carri K.; Kishan, Amar U.; et al.
Abstract: Radiation therapy (RT) continues to play an important role in the treatment of cancer. Adaptive RT (ART) is a novel method through which RT treatments are evolving. With the ART approach, computed tomography or magnetic resonance (MR) images are obtained as part of the treatment delivery process. This enables the adaptation of the irradiated volume to account for changes in organ and/or tumor position, movement, size, or shape that may occur over the course of treatment. The advantages and challenges of ART maybe somewhat abstract to oncologists and clinicians outside of the specialty of radiation oncology. ART is positioned to affect many different types of cancer. There is a wide spectrum of hypothesized benefits, from small toxicity improvements to meaningful gains in overall survival. The use and application of this novel technology should be understood by the oncologic community at large, such that it can be appropriately contextualized within the landscape of cancer therapies. Likewise, the need to test these advances is pressing. MR‐guided ART (MRgART) is an emerging, extended modality of ART that expands upon and further advances the capabilities of ART. MRgART presents unique opportunities to iteratively improve adaptive image guidance. However, although the MRgART adaptive process advances ART to previously unattained levels, it can be more expensive, time‐consuming, and complex. In this review, the authors present an overview for clinicians describing the process of ART and specifically MRgART.